Some aspects of the ecology of the Eastern Cape rocky Sandelia Bainsii (Pisces : Anabantidae) in the Tyume River, Eastern Cape, South Africa - Mayekiso, Monde (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1986)
This is an account of some aspects of the ecology of the eastern Cape rocky, Sandelia bainsii Castelnau in the Tyume river in the eastern Cape. Previous unpublished work carried out by the Zoology Department of the University of Fort Hare in the mid-seventies indicated that the species was rare in the Tyume river. Because of its uncertain conservation status, its restricted geographic distribution and the lack of information on its biology, demography, feeding and reproductive biology were studied. The species occurs in the upper, middle and lower reaches of the Tyume river and is common in rocky , shallow habitats in the middle reaches of the system. The most important threats to the survival of S. bainsii appear to be habitat alteration and alien species. The presence of these threats and the small size of the population suggest that the species may be vulnerable to local extinction. As the total range of the species extends to only a few rivers in the eastern Cape, the species might face extinction if these threats are faced throughout its range. A detailed study on the autecology of S. bainsii was therefore carried out in order to provide a basis for rational conservation and management of the remaining populations of the species.The age structure and the growth rate of S. bainsii was determined using checks on scales and otoliths. Males grow faster and reach a larger size than females. The maximum length of S. bainsii is compared to that of other anabantids. The longevity of males is 5 years and that of females 3 years. Food preferences were determined by three different methods and the indices of relative importance of food items calculated for different length groups and seasons. S. bainsii was found to be an euryphagous and opportunistic predator whose diet consists largely of insects. A considerable overlap was found between the diet of S. bainsii and that of the two alien species, Salmo gairdneri and Micropterus salmoides which indicates a possibility of competition for food. Mark and recapture experiments showed that S. bainsii is a "sedentary " species which is unlikely to be seriously affected by man-made barriers to fish migration, such as weirs. The species reaches maturity during its second growing season (males 80 - 89mm and females 60 - 69mm) and the length at maturity is related to the modal length of males and females. A large proportion of the fish are thus mature at any given time. The fish spawn repeatedly during the summer breeding season, October to February resulting in near continuous recruitment. The possible adaptive value of this habit is discussed. An attempt is made to evaluate the life history style of S. bainsii in terms of the theory of r - and K- selection and altricial and precocial life history styles
Keywords: Anabantidae; Perciformes; Labyrinth fishes